2016
DOI: 10.1002/jcu.22434
|View full text |Cite|
|
Sign up to set email alerts
|

Speckle tracking echocardiography predicts early subclinical anthracycline cardiotoxicity in patients with breast cancer

Abstract: Anthracycline treatment induces early deterioration of LV global longitudinal and circumferential strain, involving also the RV. Early change in the GLS seems to be a good predictor of the development of chemotherapy-induced cardiotoxicity. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 45:222-230, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
15
0
2
Order By: Relevance
“…A 15% change from the initial value is considered to be clinically significant (4). Changes in LV strain after RT have been described earlier, but their prognostic impact is unclear (8,9). In our patients, the initial GLS change persisted in the three-year follow-up, which may implicate permanent damage.…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 48%
“…A 15% change from the initial value is considered to be clinically significant (4). Changes in LV strain after RT have been described earlier, but their prognostic impact is unclear (8,9). In our patients, the initial GLS change persisted in the three-year follow-up, which may implicate permanent damage.…”
Section: Changes In Apical Strain In the Follow-up According To Brementioning
confidence: 48%
“…Критериями кардиотоксичности служило снижение ФВ ЛЖ менее, чем на 53 %, либо снижение ОБЗОРЫ § показателя глобальной продольной деформации на 10 % от исходных значений. В исследовании было показано, что снижение глобальной продольной деформации на 13,8 % от исходных значений было самым сильным индикатором развития кардиотоксичности (чувствительность -93 %; специ фичность -84 %) [36].…”
Section: Discussionunclassified
“…76,79,103 An 8% reduction defines patients with low risk of subclinical damage, but between 8-15% does not rule out patients at risk. [126][127][128][129] In addition, changes in circumferential deformation have been associated with a higher probability of toxicity in women who received treatment for BC (RR of 31% for every 1% reduction compared to baseline). 130 • Echocardiogram in the follow-up.…”
Section: Using Imaging Techniques To Diagnose Cardiac Damagementioning
confidence: 99%
“…132 Since the endocardium is the most vulnerable structure to the toxic effects of chemotherapy, assessment of myocardial deformation with GLS surveillance may become the most sensitive strategy for early detection of CT. 79,126,127 It has been reported that the reduction of GLS>15% from baseline at three months, predicts LVEF drop with 79% sensitivity and 82% specificity. 129…”
Section: Using Imaging Techniques To Diagnose Cardiac Damagementioning
confidence: 99%